2005
DOI: 10.1051/0004-6361:20041975
|View full text |Cite
|
Sign up to set email alerts
|

Spin vector orientations of galaxies in seven Abell clusters of BM type III

Abstract: Abstract.We present an analysis of the spatial orientations of 851 galaxies in 7 Abell clusters of BM type III (type III in the Bautz-Morgan system). Anisotropy is found in all 7 clusters. It is found that the spin vector orientations of the galaxies in the clusters of BM type III tend to be oriented both parallel (Abell 1412, Abell 2048 and Abell 4038) and perpendicular (Abell 2061, Abell 2065, Abell 2151 and Abell 2197) to the local supercluster plane. The spin vector projections of galaxies in 5 clusters (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 19 publications
2
47
1
Order By: Relevance
“…We have used a database of 5398 LSC galaxies (RV < 3000 km s −1 ) compiled by Aryal and Saurer (2005a). They used 20 catalogues for the compilation.…”
Section: The Sample: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used a database of 5398 LSC galaxies (RV < 3000 km s −1 ) compiled by Aryal and Saurer (2005a). They used 20 catalogues for the compilation.…”
Section: The Sample: Data Reductionmentioning
confidence: 99%
“…In this sense, chirality is symmetry and it depends on the true structure of the object, rather than on the physical space where it is embedded. Aryal and Saurer (2005a) classified spiral and barred spirals into 10 subsamples according to the ages of their arms and studied spatial orientation of galaxies in the Local Supercluster. They noticed anisotropy for the subsamples of latetype spirals and barred spirals.…”
Section: Introductionmentioning
confidence: 99%
“…6. A random simulation for 10 7 virtual particles (i.e, galaxies) carried out successfully by using 4 GB RAM pc. We intend to carry out simulation generating 10 8 virtual galaxies in order to find out sufficiently smooth expected isotropic distribution curves in the future.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Virgo cluster galaxies show a preferred alignment: the galactic rotation axes of leading and trailing structures are found to lie in the equatorial plane. Aryal & Saurer (2005a) noticed a preferred alignment for the late-type spirals and barred spirals in the LSC. In addition, they found that the spin vector (SV) projections of early-and late-type spirals show opposite alignment.…”
Section: Introductionmentioning
confidence: 99%
“…No significant dominance from a random distribution is noticed. Aryal & Saurer (2005a) studied the spatial orientations of SVs of 4073 galaxies in the LSC. No preferred alignment is found.…”
Section: Winding Sense Of Spiralsmentioning
confidence: 99%